STATUS TAKSONOMI IKAN NOMEI DARI PERAIRAN TARAKAN, KALIMANTAN UTARA BERDASARKAN GEN 16S rRNA SEBAGAI UPAYA KONSERVASI IKAN LAUT LOKAL INDONESIA - Endik Deni Nugroho; Dwi Anggorowati Rahayu (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2015)
Tarakan waters have geographical and landscape that supported a wealth of abundant and diverse fish. One of the natural resources on the Tarakan Island is Nomei fish. This fish is known by local names of Pepija or Lembe-Lembe. Nomei fish catch has decreased since 2009. There has been no real effort in determining the fish conservation strategies. Data on Nomei taxonomy is still lacking, so far limited research has been conducted only on bio ecology aspect. The purposed of this study was to determine the taxonomic status of Nomei fish from Tarakan based on 16S rRNA gene sequences and determine relationship with closely related species. Genetic data collection were done by taking two individual pectoral fin from each fish from Amal and Juata waters. Total DNA isolated using Roche KIT with some modifications. 16S rRNA gene amplification were done by using a universal primer. Alignment results showed that there were several automorfi nucleotide characters distinguishing of this genus. Based on 16S rRNA gene sequences with consistency of phylogenetic topology is generated, it can be concluded that Nomei fish from Amal and Juata included in Harpodon genus, species Harpodon nehereus. This is consistent with the description of morphological characters were Harpodon nehereus. It is also strengthened by divergent sequences of Harpodon sp. Amal 1 and Harpodon sp. Amal 2 (0%); while Harpodon sp. Juata 1 and Harpodon sp. Juata 2 (0%). Keywords : taxonomic status, Nomei fish, 16S rRNA gene, conservation